Cancer incidence among the NATO peacekeeping forces in Bosnia and Kosovo: a systematic review and metanalysis - Cocco, Pierluigi (La Medicina del Lavoro, 2022)
Background: A few cohort studies of the NATO peacekeepers in the Bosnia and Kosovo war reported inconclusive results on cancer risk. A systematic review and metanalysis of such studies might help to resolve the interpretative limitations. Methods: Relevant publications were retrieved through a PubMed search and from the list of references of the selected reports. Five epidemiological studies, one each from Denmark, Italy, the Netherlands, Norway, and Sweden, satisfied the selection criteria. Random and fixed effect estimators were calculated. Heterogeneity across studies was formally tested for all cancer outcomes. Results: Incidence of all cancers was below the expectation, as was the case for lung cancer and cancer at most other organs. The incidence of Hodgkin’s lymphoma exceeded expectation in the first years after deployment in the Italian cohort but not in the subsequent years of follow-up. The risk of colorectal cancer and bone cancer was increased in the Danish cohort, and so was the risk of leukaemia in the Swedish cohort. Bladder cancer cases were non significantly more than expected in the three Scandinavian studies. The Cochrane’s Q-test was indicative of significant heterogeneity across studies for total cancer, colorectal cancer, melanoma, and leukaemia. The meta-estimate of risk of bladder cancer was increased two-fold (fixed effect summary [FES] = 2.16 (95% CI 1.35 – 2.97), based on three studies. Discussion: Exposure to depleted uranium, metals, and ultrafine particles has been claimed as responsible for the cancer cases observed among peacekeepers. None of these would account for the excess of bladder cancer. The hypothesis of viral epidemics around the deployment area of the Italian military as contributing to the temporary excess of Hodgkin’s Lymphoma cases would be worth exploring.